2011
DOI: 10.3168/jds.2011-4590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor-β on mammary remodeling during the dry period of dairy cows

Abstract: Mammary remodeling in dairy cows involves coordinated changes in stromal and epithelial tissue. Tissue remodeling is characterized by changes in cell proliferation, activation of fibroblasts into myofibroblasts, and changes in extracellular matrix content. Transforming growth factor β-1 (TGF-β1) increases differentiation of fibroblasts to myofibroblasts, regulates expression of extracellular matrix proteins and proteases, and has cell-type dependent effects on proliferation. The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
(45 reference statements)
0
17
0
1
Order By: Relevance
“…Further, with the strong evidence 145 supporting TGFβ1's effects on both the stromal and parenchymal compartments of the mammary 146 gland, a more holistic approach to studying TGFβ1 signalling incorporating both stromal and 147 epithelial cells may be necessary to study novel approaches to increasing milk production. In 148 vitro treatment of whole tissue explants (De Vries et al, 2011, Magro et al, 2017 is an attractive 149 possibility, as they may convey key mechanistic information impossible to obtain by analysis of 150 biopsies. Another alternative is the use of three-dimensional co-culture models that incorporate 151 ECM and stromal cells of interest in addition to the epithelial cells, as those recently developed 152 by our group (Pallegar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further, with the strong evidence 145 supporting TGFβ1's effects on both the stromal and parenchymal compartments of the mammary 146 gland, a more holistic approach to studying TGFβ1 signalling incorporating both stromal and 147 epithelial cells may be necessary to study novel approaches to increasing milk production. In 148 vitro treatment of whole tissue explants (De Vries et al, 2011, Magro et al, 2017 is an attractive 149 possibility, as they may convey key mechanistic information impossible to obtain by analysis of 150 biopsies. Another alternative is the use of three-dimensional co-culture models that incorporate 151 ECM and stromal cells of interest in addition to the epithelial cells, as those recently developed 152 by our group (Pallegar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whether TGFβ1 disrupts tight junctions in the bovine mammary gland, and whether this is responsible for TGFβ1-induced apoptosis in the involuting bovine mammary gland, remains to be addressed. TGFβ1 and its receptors are upregulated during bovine involution (Plath et al, 1997), and in vitro findings suggest that elevated TGFβ1 expression during involution is due in part to its increased secretion by bovine mammary cells during the transition from lactation to the dry period (Zarzyńska, Gajewska & Motyl, 2005), as well as through enhanced release of TGFβ1 from the extracellular matrix (ECM) (De Vries et al, 2011). TGFβ1 arrests bovine epithelial cell growth (Kolek et al, 2003) and such effect of TGF was shown to be important for the development of fully functional mammary glands in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Further, with the strong evidence supporting TGFβ1's effects on both the stromal and parenchymal compartments of the mammary gland, a more holistic approach to studying TGFβ1 signalling incorporating both stromal and epithelial cells may be necessary to study novel approaches to increasing milk production. In vitro treatment of whole tissue explants (De Vries et al, 2011, Magro et al, 2017 is an attractive possibility, as they may convey key mechanistic information impossible to obtain by analysis of biopsies. Another alternative is the use of three-dimensional co-culture models that incorporate ECM and stromal cells of interest in addition to the epithelial cells, as those recently developed by our group (Pallegar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os TGF-βs compreendem uma família de polipeptídios que incluem os TGF-β1, TGF-β2 e TGF-β3, possuindo a função de regular o desenvolvimento do tecido mamário (VRIES et al, 2011). A forma predominante no leite é a TGF-β2 (85%), apresentando-se ligada a uma proteína e com dímeros com 224 aminoácidos e 25000 Da, após ati vação ácida, sendo que quatro ligações dis sulfeto estabilizam cada monômero e uma ligação dissulfeto estabiliza o dímero.…”
Section: Introductionunclassified